Pelvic and peritoneal hydatidosis: An uncommon presentation of the common entity - Milan Kc; Ishwor Regmi; Alok Kumar Jha; Biraj Pokhrel; Roshan Pathak; Ashutosh Kashyap; Siddinath Gyawali; Deepika Rijal; Laligen Awale; Abhishek Bhattarai; Prasan Bir Singh Kansakar (Clinical Case Reports, 2023)
Key Clinical Message The pelvic and peritoneal hydatidosis occurs mostly after the traumatic rupture or surgical spillage of Echinococcus from liver or spleen. The treatment is surgical aiming to eradicate local disease, preventing complications, and reducing recurrences. Abstract We report a unique case of a 26‐year‐old male who presented with acute urinary retention and abdominal distention. Later, CT‐urography revealed peritoneal and pelvic hydatidosis behind this presentation, which was managed surgically.